CAWA LAMPUNG : KAMUS BAHASA INDONESIA-LAMPUNG DIALEK A BERBASIS ANDROID - Febi Eka Febriansyah; Ardiansyah Ardiansyah; Afan Darmaji (Lambung Mangkurat University, 2020)
Indonesia is country rich in cultural diversity, one of which is regional languages. In the Law of the Republic of Indonesia Number 24 of 2009 article 1 paragraph 6, what is meant by regional languages is the language used for generations by Indonesian citizens in regional areas in the territory of the Unitary State of the Republic of Indonesia. There are many regional languages in Indonesia, one of which is Lampung. however, the reduction in Lampung language speakers can cause the Lampung language to disappear. With the help of technology, especially Android, it can help to increase interest in Lampung language, especially in Lampung adolescents. this research will develop an Indonesian translator application to the Lampung dialect A on the Android Platform. The application is named Cawa Lampung. the translation process is carried out by the system with word translation. Every word is carried out the stemming process using the Nazief Adriani stemming method. The system development method used is eXtreme Programming. From the functional test results, all functions went well, and from the nonfunctional results it has a value of 85.57% which means